Social tourism and self-efficacy: exploring links between tourism participation, job-seeking and unemployment - Kakoudakis, Konstantinos I.; McCabe, Scott; Story, Vicky (Elsevier, 2017)
Social tourism is assumed to provide important psychological benefits for economically and socially disadvantaged populations. This study examines empirically whether these individual benefits are associated with socioeconomic benefits to society by focusing on unemployed individuals. Psychological benefits are addressed in terms of self-efficacy, and socioeconomic benefits, in terms of job-search behaviour. Findings from mixed-methods data reveal that holidays create enabling environments, which bring about positive changes in participants’ self-efficacy, contributing to positive effects on their job-search behaviour. Positive effects are also identified with regard to behaviours towards alternative paths to employment, such as volunteering. Given that these behavioural changes comprise major determinants of reemployment, it is suggested that social tourism may hold potential for incorporation into existing unemployment policies.